Immunotherapy for Platinum-Resistant Ovarian Cancer as a Glimmer of Hope - Jan Brancewicz; Irena Barbara Padzińska-Pruszyńska; Małgorzata Kubiak; Paulina Kucharzewska (Cells, 2025)
Ovarian cancer is a leading cause of cancer-related deaths among women, with platinum resistance posing a significant challenge. Conventional therapies often fail in these cases, highlighting the urgent need for novel treatment approaches. Immunotherapy has emerged as a promising strategy, offering renewed hope for patients with platinum-resistant ovarian cancer (PROC). This review explores the current landscape of immunotherapies for PROC, discussing different approaches, their mechanisms of action, and the potential for overcoming the limitations of conventional treatments.